Implementasi Aplikasi Manajemen Wisata Pantai Berbasis Mobile dengan Model Waterfall - Kaka Nisfa Kurniawan; Rr Hajar Puji Sejati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Pangandaran Beach is one of the leading tourist destinations in West Java, boasting significant tourism potential. However, the increasing number of tourist visits has created various problems, such as environmental pollution due to waste and a manual ticket booking system. This has reduced visitor comfort and reduced the effectiveness of tourism area management. This research aims to develop a web-based and mobile-based waste reporting and ticket management system as a solution to these problems. The designed system allows tourists and the public to report waste directly through the application and book tickets online with QR code validation. The research used a software engineering approach with a literature review method as the basis for system design. The results indicate that this system has the potential to improve tourism management efficiency, expedite ticketing services, and support environmental conservation at Pangandaran Beach. Therefore, the use of information technology can be an effective strategy in realizing sustainable and environmentally friendly tourism.